Maternal vitamin D deficiency affects the morphology and function of glycolytic muscle in adult offspring rats. Issue 4 (18th May 2022) - Reis, Natany G.; Assis, Ana P.; Lautherbach, Natália; Gonçalves, Dawit A.; Silveira, Wilian A.; Morgan, Henrique J.N.; Valentim, Rafael R.; Almeida, Lucas F.; Heck, Lilian C.; Zanon, Neusa M.; Koike, Tatiana E.; Santos, Audrei R.; et al.
Abstract: Background: Fetal stage is a critical developmental window for the skeletal muscle, but little information is available about the impact of maternal vitamin D (Vit. D) deficiency (VDD) on offspring lean mass development in the adult life of male and female animals. Methods: Female rats (Wistar Hannover) were fed either a control (1000 IU Vit. D3/kg) or a VDD diet (0 IU Vit. D3/kg) for 6 weeks and during gestation and lactation. At weaning, male and female offspring were randomly separated and received a standard diet up to 180 days old. Results: Vitamin D deficiency induced muscle atrophy in the male (M‐VDD) offspring at the end of weaning, an effect that was reverted along the time. Following 180 days, fast‐twitch skeletal muscles [ extensor digitorum longus (EDL)] from the M‐VDD showed a decrease (20%; P < 0.05) in the number of total fibres but an increase in the cross‐sectional area of IIB (17%; P < 0.05), IIA (19%; P < 0.05) and IIAX (21%; P < 0.05) fibres. The fibre hypertrophy was associated with the higher protein levels of MyoD (73%; P < 0.05) and myogenin (55% %; P < 0.05) and in the number of satellite cells (128.8 ± 14 vs. 91 ± 7.6 nuclei Pax7 + in the M‐CTRL; P < 0.05). M‐VDD increased time to fatigue during ex vivo contractions of EDL muscles and showed an increase in the phosphorylation levels of IGF‐1/insulin receptor and their downstream targets related to anabolic processes and myogenic activation, including Ser 473 Akt and Ser 21/9 GSK‐3β. In such muscles, maternal VDD induced a compensatory increase in the content of calcitriol (two‐fold; P < 0.05) and CYP27B1 (58%; P < 0.05), a metabolizing enzyme that converts calcidiol to calcitriol. Interestingly, most morphological and biochemical changes found in EDL were not observed in slow‐twitch skeletal muscles (soleus) from the M‐VDD group as well as in both EDL and soleus muscles from the female offspring. Conclusions: These data show that maternal VDD selectively affects the development of type‐II muscle fibres in male offspring rats but not in female offspring rats and suggest that the enhancement of their size and fatigue resistance in fast‐twitch skeletal muscle (EDL) is probably due to a compensatory increase in the muscle content of Vit. D in the adult age.